P-176 'Blurred boundaries' – partnership working in hospice care. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Forbes, Jane
Abstract : Although agencies may be in partnerships where they have formalised contracts, it is when they collaborate – that is they work together, that the impact will be seen. Identifying the growing needs of patients within our communities, this case presentation will explore how collaborative working between charities, the NHS, and social and private care strengthens our flexibility to adapt to those needs. Ellis (2015) states 'good care means that people get the right services, at the right time, in the right way'. Many hospices work with other providers in the statutory and voluntary sectors, and such partnerships are central to getting care right in the future. Hospice UK (2013) suggests that as small organisations hospices are inherently flexible and should capitalise on their ability to experiment with new ideas, turning them into action. Following the disease trajectory of a patient with advanced Motor Neurone Disease with emotional and physical complexities, whose package of care was no longer sustainable at home due to impact and distress on carers, Nightingale House Hospice decided to examine a new initiative. In discussion with other agencies the idea was proposed to transfer the patient to the hospice in-patient unit, and to transfer her package of care from other providers to be further supported by us as a specialist team. This initiated effective collaboration between organisations to support the patient's needs and her preferred place of care and death while sharing financial and emotional impact on each agencies resources. NHS Wales (2007) propose that effective collaboration relies on trust, appropriate leadership, and the need at the outset of collaborative initiatives to understand the reasons organisations seek to work together. A number of factors needed to be explored and central to this were the patient and her family, and acknowledging the advance care planning wishes she had made.